Perceptions on the Implementation of the Integrated Territorial Investment Mechanism (ITI) and Its Impact on Sustainable Development and Resilience of Danube Delta - Alina Georgiana Profiroiu; Corina Cristiana Nastacă; Mirela Caraman (Pufleanu) (Transylvanian Review of Administrative Sciences, 2021)
The Integrated Territorial Investment mechanism (ITI) was implemented in Romania to the territory of ITI Danube Delta in the 2014-2020 programming period. In this respect, the present article aims to analyze the process of implementation of the ITI mechanism on the Danube Delta territory in order to find out the impact of its implementation on the socio-economic development of the area and on its resilience, as well as the main problems encountered by the responsible authorities for managing this programme and the beneficiaries of these funds. The research methodology consists of a survey conducted by using two questionnaires designed by the authors. The study had 42 participants from the fund managers’ category and 71 participants from the beneficiaries’ group. The study revealed a positive perception among all the participants which considered that ITI impacts the resilience of the Danube Delta territory to a medium extent. The most important problems encountered in the implementation process were the pre-financing process, the guides’ conditions that are not adapted to the beneficiaries’ needs and the public procurement process. The research revealed a high degree of satisfaction from both types of respondents regarding the ITI mechanism and a good relation between the managing institutions and beneficiaries.